Magnetic field observations in CoFeB/Ta layers with 0.67-nm resolution by electron holography. Issue 1 (December 2017) - Tanigaki, Toshiaki; Akashi, Tetsuya; Sugawara, Akira; Miura, Katsuya; Hayakawa, Jun; Niitsu, Kodai; Sato, Takeshi; Yu, Xiuzhen; Tomioka, Yasuhide; Harada, Ken; Shindo, Daisuke; Tokura, Yoshinori; et al.
Abstract Nanometre-scale magnetic field distributions in materials such as those at oxide interfaces, in thin layers of spintronics devices, and at boundaries in magnets have become important research targets in materials science and applied physics. Electron holography has advantages in nanometric magnetic field observations, and the realization of aberration correctors has improved its spatial resolution. Here we show the subnanometre magnetic field observations inside a sample at 0.67-nm resolution achieved by an aberration-corrected 1.2-MV holography electron microscope with a pulse magnetization system. A magnetization reduction due to intermixing in a CoFeB/Ta multilayer is analyzed by observing magnetic field and electrostatic potential distributions simultaneously. Our results demonstrate that high-voltage electron holography can be widely applied to pin-point magnetization analysis with structural and composition information in physics, chemistry, and materials science.